Pengaruh Pengembangan Sumber Daya Manusia Dalam Meningkatkan Produktivitas Karyawan PT. BRI (PERSERO), TBK Cab. Bangkalan - Laili Nur Rahmawati; Iriani Ismail; Mudji Kuswinarno (Trunojoyo University of Madura, 2014)
The productivity associated with the level of the companies progress. If the employee doesn’t get human resources development, the advancement of companies can’t develop. The hypothesis of this research was suspected education (X1) and training (X2) effect on productivity, as well as education as the dominant variables. The purpose of this study was examine the influence of education and training towards productivity. As well as researching the affecting education variables are dominant. Based on analysis using multiple linear regression test obtained results, education effect on the productivity rate was 78.5%. Training effect on the productivity rate was 36.4%. Results of determination multiple koefesien (R2) by 0,740, shows that the percentage of the influence of education and training for employee productivity amounting to 74%. While 26% are affected by other variables that are not included in this research model. From the results of this research, education have dominant effect 0.785 because it was major requirement for job promotion.